2013
DOI: 10.1111/joa.12093
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of duodenojejunal flexure formation in mice: implications for understanding the genetic basis for gastrointestinal morphology in mammals

Abstract: The mammalian gut undergoes morphological changes during development. We studied the developing mouse duodenojejunal flexure (DJF) to elucidate the mechanism of formation. During embryonic days 10.75-13.75, DJF formation was morphologically classified into three stages: the expansion stage, flexure formation stage, and flexure elongation stage. From the expansion to the flexure formation stages, the DJF wall showed asymmetric morphology and proliferation along the left-right intestinal axis. From the flexure f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The differences in the distribution of positively reacted cells were represented as the difference in optical densities. Optical densities were evaluated as the percentage of mean number of pixels versus the correlated value at which the pixel of the respective intensity was present (Onouchi et al, 2013;Varghese et al, 2014).…”
Section: Morphometric and Statistical Analysismentioning
confidence: 99%
“…The differences in the distribution of positively reacted cells were represented as the difference in optical densities. Optical densities were evaluated as the percentage of mean number of pixels versus the correlated value at which the pixel of the respective intensity was present (Onouchi et al, 2013;Varghese et al, 2014).…”
Section: Morphometric and Statistical Analysismentioning
confidence: 99%
“…In mice, similar mesenchymal and epithelial changes are seen here that seem to drive the curvature independently of the dorsal mesentery (Onouchi et al , 2016, Onouchi et al , 2015). However, whereas differential proliferation does not seem to be present in the DM or curving stomach, it does seem to be a driving force for DJF formation as the outer curvature shows increased cell divisions that create a bend in the gut tube (Onouchi et al , 2013). Whether Pitx2-mediated sculpting of the stomach or other organs is at play in the chick is currently unknown.…”
Section: Looping Morphogenesismentioning
confidence: 99%
“…For example, the cranial suspensory ligament of the gonads regresses in males for testis descent and is maintained in females to keep the ovary in the abdominal cavity during development (Emmen et al, 1998). Hence, the smooth muscle bundle in the mouse duodenocolic fold also seems to play a role to keep the ascending duodenum in the abdominal cavity because the duodenum in animals is suspended by mesoduodenum freely in the abdominal cavity and did not belong to a retroperitoneal organ in contrast to human, and the bundle might play a role relating morphogenesis of the ascending duodenum and the caudal duodenal flexure during development (Onouchi et al, 2013, 2015, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…As important players of gut morphogenesis, we consider the gut tube itself and factors outside of the gut tube such as the gut mesentery. In the previous studies, we reported that the mouse duodenojejunal flexure (DJF) was formed by asymmetric morphogenesis between the inner and outer bending sides of the DJF (Onouchi et al, 2013, 2015, 2016). After the DJF formation, the DJF proceeds to the flexure elongation phase, characterized by an elongated flexure around the stomach to form the caudal flexure of the duodenum and the ascending duodenum part (Onouchi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%